Developing a quality and safety surveillance system: A protocol for a realist review and synthesis of the literature. - Busra Ertugrul; Jaspreet Kaur Dullat; Therese McDonnell; Marcella O'Dowd; Eilish McAuliffe (PLoS ONE)
Background Patient harm as a result of unsafe care remains a growing global health concern, and traditional efforts prioritising tracking errors and voluntary reporting to detect adverse events result in very low error detection rates. In attempting to address this, some countries have developed patient safety surveillance systems where several data sources are combined and interrogated to detect errors and deterioration as well as to highlight good practices. The development of such systems requires overcoming various technological, executive, financial, political, and behavioral challenges. The process of developing quality and safety surveillance systems is an important one that is worthy of research that enables the sharing of learning with countries embarking on the development of such a system. Aim This is the protocol of the realist review that aims to develop a programme theory that explores the underlying mechanisms and processes for developing a quality and safety surveillance system in healthcare settings. Design This paper presents the research protocol for the quality and safety surveillance system development. The realist synthesis method will be used to synthesize the evidence in the literature. Methods Initial programme theory will be developed based on a literature review, stakeholder consultations with the programme designers and developers, project meetings, the theory of change model that underpins the programme, and an understanding of systems theory to identify the context and mechanisms that cause quality and safety surveillance systems to succeed or fail in general healthcare settings. Three-phase iterative searches of PubMed, PsycInfo, Central, CINAHL, and Grey literature will be conducted. The studies in any setting and for any patient group will be included. The snowball technique will also be used to search the reference list of the related studies. The search period ranges from 1 January 2000 to 31 December 2023. Results will be reported following RAMESES and PRISMA-ScR guidelines.